Strain-Specific Anti-Inflammatory Effects of Faecalibacterium prausnitzii Strain KBL1027 in Koreans - Seo, Boram; Jeon, Kyungchan; Kim, Woon-Ki; Jang, You Jin; Cha, Kwang Hyun; Ko, GwangPyo (Springer Pub. Co., 2025)
Faecalibacterium prausnitzii is one of the most dominant commensal bacteria in the human gut, and certain anti-inflammatory functions have been attributed to a single microbial anti-inflammatory molecule (MAM). Simultaneously, substantial diversity among F. prausnitzii strains is acknowledged, emphasizing the need for strain-level functional studies aimed at developing innovative probiotics. Here, two distinct F. prausnitzii strains, KBL1026 and KBL1027, were isolated from Korean donors, exhibiting notable differences in the relative abundance of F. prausnitzii. Both strains were identified as the core Faecalibacterium amplicon sequence variant (ASV) within the healthy Korean cohort, and their MAM sequences showed a high similarity of 98.6%. However, when a single strain was introduced to mice with dextran sulfate sodium (DSS)-induced colitis, KBL1027 showed the most significant ameliorative effects, including alleviation of colonic inflammation and restoration of gut microbial dysbiosis. Moreover, the supernatant from KBL1027 elevated the secretion of IL-10 cytokine more than that of KBL1026 in mouse bone marrow-derived macrophage (BMDM) cells, suggesting that the strain-specific, anti-inflammatory efficacy of KBL1027 might involve effector compounds other than MAM. Through analysis of the Faecalibacterium pan-genome and comparative genomics, strain-specific functions related to extracellular polysaccharide biosynthesis were identified in KBL1027, which could contribute to the observed morphological disparities. Collectively, our findings highlight the strain-specific, anti-inflammatory functions of F. prausnitzii, even within the same core ASV, emphasizing the influence of their human origin.